Clinical considerations for the use of FLT3 inhibitors in acute myeloid leukemia. (September 2019) - Weis, Taylor M.; Marini, Bernard L.; Bixby, Dale L.; Perissinotti, Anthony J.
Abstract: Internal tandem duplications and tyrosine kinase mutations in the fms-like tyrosine kinase 3 (FLT3) receptor can occur in acute myeloid leukemia (AML) and portend a poor prognosis. Midostaurin, a multikinase inhibitor that targets FLT3, demonstrated a survival benefit in FLT3-mutated AML in combination with front-line chemotherapy. Despite this advancement, the use of FLT3 inhibitors in clinical practice is complicated by significant drug-drug interactions and uncertainty about optimal timing, duration, and sequencing of therapy. As monotherapy, the utility of FLT3 inhibitors was initially limited by incomplete and transient clinical responses and the development of acquired resistance. This led to the development of more potent and selective FLT3 inhibitors designed to overcome common resistance mechanisms. One of these second generation FLT3 inhibitors, gilteritinib, is now FDA-approved for the treatment of relapsed or refractory AML. Now that multiple FLT3 inhibitors are commercially available, it is important to further delineate the role of these agents in the AML population. This review aims to provide a comprehensive overview of the role of FLT3 inhibitors in AML and apply the current literature to clinical practice.